Sharia-Based Risk Management: A Literature Review on Its Impacts and Potential in Supporting Sustainable Economy - Siagian, Riza Rasyid Al-Aufa; K, Kamilah (Yayasan Sagita Akademia Maju, 2025)
This study explores the concept of Sharia-based risk management and its potential role in fostering sustainable economic development. By synthesizing recent literature, the research identifies core principles, impacts, and challenges associated with the application of Sharia-compliant risk management practices in various sectors, including finance, trade, and industry. The findings highlight the alignment of Sharia principles with sustainability objectives, offering innovative insights into risk mitigation strategies that promote ethical and equitable economic growth. This paper also proposes a framework for integrating Sharia-based risk management into global sustainability practices.